Development of Indonesian Realistic Mathematics Education-Based Student Worksheets to Measure Students’ Mathematical Problem-Solving Abilities - Refianti, Rani; Luthfiana, Maria; Adha, Idul (Edumatica : Jurnal Pendidikan Matematika, 2026)
The design and creation of student worksheets based on the Indonesian Realistic Mathematics Education approach is the primary focus of this research. The goal is for these worksheets to meet the requirements of usability, validity, and efficacy for improving junior high school students’ mathematical problem-solving abilities. The chronological framework employed in this study follows the ADDIE model, specifically targeting seventh-grade students and addressing linear equations with two variables. The validity of the developed product was assessed by experts in the fields of language, Material, and media, resulting in Aiken’s V coefficients of 0.69, 0.73, and 0.70, respectively. These coefficients indicate that the worksheets are considered valid as per expert evaluations. To measure practicality, feedback was collected from both teachers and students via response questionnaires. The results indicated a high level of practicality, with 80% of teachers and a notable 80.05% of students expressing positive responses. Overall, these findings suggest that the developed worksheets are appropriate for classroom implementation and have the potential to support effective mathematics learning.